Bruxelles, une « ville inclusive », mais pour qui ? - Alexandre Donnen (Genre, Sexualité et Société)
Through an intersectional analysis, this article questions the transformation of Brussels into an “inclusive city” for sexual minorities. In a context of inter-urban competition, it shows that the implementation of the “inclusive city” finds an echo in the new challenges posed by the urban management transformation: economic and tourist development, brand image, settlement, attractiveness, etc. This implementation thus generates a cohabitation between recognition and instrumentalization logics of sexual minorities. In this context, queer spaces today are seen as a resource for urban development, even in historically downgraded neighborhoods that are, a priori, far removed from queer imaginations. However, the implementation of the “inclusive city” produces hierarchies between minorized groups, depending on who is designated as a value producer. Thus, the article underlines how the implementation of the “inclusive city” builds “winning” and “losing” communities, inscribed in class, gender and race relations.